Growth Performance Of Planted Shorea Macrophylla Under Line Planting Technique - Mayuran, Perumal; Mohd Effendi, Wasli; Hamsawi, Sani; Abas, Said; Hafsah, Nahrawi (2012)
A study on the growth performance and survival rate of planted Shorea macrophylla of different age stands was conducted at Sampadi Forest Reserve, Sarawak. The objectives of this study were to assess the growth performance and survival rate of planted S. macrophylla under reforestation activities that were implemented by Forest Department, Sarawak along with several agencies of Japan as to obtain preliminary data for further improvement of future reforestation activities in Sarawak. In this study, S. macrophylla planted under line planting method was selected. Study plots were established in the reforestation areas (planted with S. macrophylla in the year 1996; SM96, 1997; SM97, 1998; SM98 and 1999; SM99). Diameter at breast height (DBH), total height and survival rate were measured. The findings indicated that the growth performance in terms of survivability and mean annual increment of diameter (MAID) in SM96 were the highest and showed better growth as compared to SM97, SM98 and SM99. On the other hand, the mean annual increment of height (MAIH) in SM97 revealed the greatest height among other plots. The survival rate of S. macrophylla in SM96, SM97, SM98 and SM99 were 89%, 81%, 77% and 51% respectively. Substantial growth performance and high survival rate of S. macrophylla implied that microclimate condition such as competition between planted and existing pioneer species of the study area may have affected the planted S. macrophylla. Notwithstanding, it is recommended that proper silvicultural technique is crucial to manage the existing pioneer tree species towards the success of this reforestation programme.